Antifungal activity of extracts, essential oil and constituents from Petroselinum crispum against Colletotrichum acutatum (2018)
The effect of extracts, essential oil, and their major constituents from parsley (Petroselinum crispum (Mill.) Fuss.) against the phytopathogenic fungus Collectotrichum acutatum was evaluated by the poisoned agar method. Results showed that all extracts, along with the essential oil, significantly inhibit the radial growth of C. acutatum at concentrations higher than 100 μg mL-1. The higher activity was found for the essential oil followed by the n-hexane extract. Analysis by gas chromatography with mass spectroscopy (GC-MS) of n-hexane extract and the essential oil of P. crispum showed that the major components correspond to the phenylpropanoids myristicin and parsley-apiole. Both compounds were isolated by conventional chromatographic techniques and their structures elucidated by spectroscopicmethods. Myristicin and parsley-apiole displayed a significant inhibitory effect against C. acutatum. The highest fungistatic activity was found to parsley-apiole with IC50 value of 40 μg mL-1. In conclusion, parsley may be a good source of antifungal compounds to control C. acutatum.